Standard of physical attractiveness - Kujawa, Betina; Strzałko, Jan (Anthropological Review, 1998)
The research was conducted in order to corroborate the validity of the hypotheses that (1) there are certain common criteria of physical attractiveness of the face, and hence divergence of assessments between persons judging attractiveness is reduced, regardless of their sex or age; (2) assessment of the physical attractiveness of human faces is a property of the cognitive system; its criteria emerge early in the course of the individual development and do not change with age; (3); the most attractive faces will be characterised with trait variants close to the mean values for a given population. Computer averaged faces will be perceived as more attractive than actually existing faces, since they bear the greatest resemblance to the mental prototype of a face.